Open days S.M.A.K. - Boog, Mark; Declercq, Miguel; Gerlach, Eva; Godijn, Wouter; Knibbe, Hester; Loontjens, Jannah; Michel, K.; Oosterhoff, Tonnus; Van hee, Miriam; Verhelst, Peter; Wieg, Rogi; Wigman, Menno; et al. (Amsterdam Gent : Roma Publications Amsterdam SMAK (Stedelijk Museum voor Actuele Kunst) Gent, 2005)
van Golden, Daan ; De Keyser, Raoul ; Ader, Bas Jan ; Kahrs, Johannes ; Currin, John ; Langelaar, Marije ; Goudzwaard, Kees ; van Riessen, Wouter ; Flanagan, Barry ; DC, Franky ; Richter, Gerhard ; Gertsch, Franz ; Rodriguez Plaza, José Maria ; Vanderheyden, JCJ ; Yun-Fei Ji
publ. SMAK : zie kast leeszaal
Nederlands
boek